Interval models of temperature characteristics of superheater separators in nuclear power plant units with the capacity of 1000 MW - Yefimov, O. V.; Potanina, T. V.; Kavertsev, V. L.; Harkusha, T. A.; Yesypenko, T. O. (Kharkov Institute of Physics and Technology, 2022)
The analysis of the influence of changes in the parameters of steam superheater separators SHS-1000 of nuclear power plant units with the capacity of 1000 MW on the efficiency and safety of their operation, including the temperature characteristics at the nominal and partial operating modes of power units, has been carried out. Based on the experimental data of the thermal tests of the power unit, the temperature characteristic of the second stage of the SHS-1000 has been constructed in the form of the dependence of the temperature change of the heated steam at the second stage of the SHS on the change in the operating mode of the power unit. To create a correct mathematical model of this dependence, taking into account the limited amount of experimental data and the uncertainty of information about the structure and the probabilistic nature of measurement error during testing, the use of numerical methods of interval analysis has been proposed. Interval analysis has allowed to obtain an interval model that describes the receiver, which contains all possible values of the dependence of temperature change of the heated steam at the second stage of SHS on the unit operating mode (the electrical load). It has been shown that in conditions of limited initial data and uncertainty of information about it, numerical methods of interval analysis allow to create interval models of operational (energy) characteristics technological processes and equipment of NPP units with the maximum possible correspondence to real processes and objects, which is important to ensure high efficiency and safe operation of power units.

Проведено аналіз впливу зміни параметрів сепараторів пароперегрівників СПП-1000 енергоблоків АЕС потужністю 1000 МВт на ефективність і безпеку їх роботи, в тому числі значень температурних характеристик на номінальному і часткових режимах роботи енергоблоків. За експериментальними даними результатів теплових випробувань енергоблоку побудована температурна характеристика другого ступеня СПП-1000 у вигляді залежності зміни температури пари, що гріється у другому ступені СПП, від зміни режиму роботи енергоблоку. Для створення коректної математичної моделі цієї залежності, враховуючи обмежену кількість експериментальних даних і невизначеність інформації про структуру і вірогідний характер помилок і похибок вимірювань під час випробувань, запропоновано застосування чисельних методів інтервального аналізу. Ці методи дозволили отримати інтервальну модель, що описує «трубку», в якій містяться всі можливі значення залежності зміни температури пари, що гріється у другому ступені СПП, від режиму роботи енергоблоку (електричної потужності). Показано, що в умовах обмеженості вихідних даних і невизначеності інформації про них чисельні методи інтервального аналізу дозволяють створювати інтервальні моделі експлуатаційних (енергетичних) характеристикта технологічних процесів, що відбуваються в устаткуванні енергоблоків АЕС, з максимально можливою їх відповідністю реальним процесам та об’єктам, що важливо для забезпечення високої ефективності і безпеки роботи енергоблоків.
Інтервальні моделі температурних характеристик сепараторів пароперегрівників енергоблоків АЕС потужністю 1000 МВт
Keywords: separators; NPP; power units; temperature; superheaters; сепаратори; АЕС; енергоблоки; температура; пароперегрівачі